Upaya peningkatan keterampilan anak balita tentang cuci tangan efektif guna pencegahan diare di Posyandu Kampung Malabar Cibadak Lebak - Tutik Iswanti; Nintinjri Husnida; Ayi Tansah Rohaeti (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
Diarrhea is an endemic disease in Indonesia and is a potential disease of Extraordinary Events (KLB) which is often accompanied by death with CFR from 2010-2017 still quite high (>1%). One of the preventions of diarrheal disease is to maintain personal hygiene by washing hands, but it was found that only about 15% of pre-school age children washed their hands with soap before and before. This community service aims to improve the skills of children under five about effective hand washing. This community service was divided into 2 meetings with the target children under five at the Posyandu Kampung Malabar, Cibadak, Lebak. At the first meeting, counseling and stimulation of effective hand washing were given. The second meeting was to evaluate how to wash hands effectively. As many as 85% of children under five can practice effective hand washing on their own without assistance. This shows an increase in skills and is statistically proven that the intervention provided can improve skills. This service activity is effective in improving the skills of children under five who previously were still many who could do effective hand washing.